KEPRIBADIAN TOKOH UTAMA DAN NILAI KERJA KERAS DALAM NOVEL RANTAU 1 MUARA KARYA FUADI SERTA RELEVANSINYA DENGAN PEMBELAJARAN APRESIASI SASTRA DI SMA - Wina Yunita; Sarwiji Suwandi; Edy Suryanto (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe and explain (1) the intrinsic element;(2) personality aspect of the main character;(3) character education; and(4) the relevance of the personality of the main character and the value of character education in the novel Rantau 1 Muara Fuadi with learning literature appreciation in High School.This research is a descriptive-qualitative research which used psychology literature approach. The data collection techniques used in this study were document analysis techniques and interviews. The data validity techniques used were data triangulation and source triangulation.The results of this research showed that the structural elements that build include: the theme of education, groove mix, setting a place located in Bandung, Jakarta, Maninjau, America, and England, the personality, the standpoint of using the technique of acknowledgment and the message to consistently pursue ideals.Through the three dimensional character is obtained figures of Alif and Dinara. The personality of the main characters in the novel, analyzed using Freud’s psychoanalytic theory which includes three personality structures Id, Ego, and Superego. Novel Rantau 1 Muara also contains the value of hard work education found on the main characters, Alif and Dinara. Novel Rantau 1 Muara is relevant to the learning of literature appreciation in high school class XII.